1991
DOI: 10.1007/bf03350244
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function evaluation by different commercially available free thyroid hormone measurement kits in term pregnant women and their newborns

Abstract: Evaluation of thyroid status by measurement of free thyroid hormone concentrations seems particularly helpful in conditions with altered serum binding proteins. In pregnancy, a condition of increased thyroxine binding globulin, serum free thyroxine (FT4) and free triiodothyronine (FT3) concentrations have been reported to be normal, increased or decreased. In the present study we have measured serum total and free thyroid hormone concentrations in pregnant women, their newborns and nonpregnant women. Serum FT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 48 publications
2
38
0
6
Order By: Relevance
“…When TBG concentrations are abnormal, FT4 estimate tests are normally preferred over TT4 immunoassay measurements. However, current non-dialysis FT4 assays are binding-protein dependent and cannot be compared in absolute terms across methods [24,25]. Serum T4 and T3 detection methods have evolved through a variety of technologies since the 1950s.…”
Section: Discussionmentioning
confidence: 99%
“…When TBG concentrations are abnormal, FT4 estimate tests are normally preferred over TT4 immunoassay measurements. However, current non-dialysis FT4 assays are binding-protein dependent and cannot be compared in absolute terms across methods [24,25]. Serum T4 and T3 detection methods have evolved through a variety of technologies since the 1950s.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy pregnant women fT4 concentrations decrease at the second and third trimester [12]. This phenomenon was considered to be a result of changes in thyroxine-binding globulin and albumin concentrations [13,14] or of a true hypothyroxinaemia, possibly reflecting iodine deficiency [15]. Brucker et al reported in women with normal thyroid function a drop of both fT4 and fT3 levels after the first trimester of pregnancy, with no influence of iodine supplementation [16].…”
Section: Rycina 1 Zmiany Stężeń Jodu W Moczu Porannym Oraz Tsh Ft4 mentioning
confidence: 99%
“…Albumin-dependent methods produce lower values (down to 50%) because serum albumin decreases in pregnant women (74,75) …”
Section: How Should Thyroid Function Tests Be Interpreted During Pregmentioning
confidence: 99%